Anesthesia With Propofol Sedation Reduces Locoregional Recurrence in Patients With Breast Cancer Receiving Total Mastectomy Compared With Non-Propofol Anesthesia - Zhang, Jiaqiang; Chang, Chia-Lun; Lu, Chang-Yun; Chen, Ho-Min; Wu, Szu-Yuan (Frontiers in Oncology, 2022)
PURPOSE: We examined locoregional recurrence (LRR) in patients with breast invasive ductal carcinoma (IDC) receiving total mastectomy (TM) under propofol-based paravertebral block-regional anesthesia (PB-RA) versus sevoflurane-based inhalational general anesthesia (INHA-GA) without propofol. All-cause death and distant metastasis were secondary endpoints. PATIENTS AND METHODS: Patients with breast IDC receiving TM were recruited through propensity score matching and categorized into INHA-GA with sevoflurane and PB-RA with propofol groups. Cox regression analysis was performed to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). RESULTS: In the multivariate Cox regression analysis, the adjusted HR (aHR; 95% CI) of LRR for the PB-RA with propofol group was 0.52 (0.28-0.96) compared with the INHA-GA with sevoflurane group. The aHRs of LRR for differentiation grade II, grade III, the American Joint Committee on Cancer clinical stage II, stage III, pathological tumor (pT) stage 2, pT stage 3–4, pathological nodal (pN) stage 1, and pN stage 2–3 were 1.16 (1.04-2.08), 1.28 (1.07-2.12), 3.71 (1.82-7.59), 4.67 (1.65-13.18), 1.09 (1.02–1.21), 1.17 (1.03–2.16), 1.10 (1.03–1.33), and 1.22 (1.06–2.41), respectively, compared with differentiation grade I, clinical stage I, pT1, and pN0. The aHR of LRR for adjuvant RT was 0.88 (0.64-0.94) compared with that for no adjuvant RT. CONCLUSION: PB-RA with propofol might be beneficial for reducing LRR in women with breast IDC receiving TM compared with INHA-GA without propofol.